2014
DOI: 10.1515/bmc-2014-0022
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation of CC-chemokine ligand 2 in nonresolving inflammation

Abstract: Inflammation mediated by the crosstalk between leukocytes and resident tissue cells is crucial for the maintenance of homeostasis. Because chemokine ligands and receptors, which recruit a variety of leukocytes, are widely distributed among tissues, it is important to understand the mechanisms regulating inflammatory disease. Chemokines such as CC-chemokine ligand 2 (CCL2) amplify and maintain inflammation through chemokine-cytokine networks after the recruitment of circulating leukocytes. Chemokine-dependent n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 113 publications
2
12
0
2
Order By: Relevance
“…[14] CCL2 amplify and maintain inflammation through chemokine-cytokine networks after the recruitment of circulating leucocytes. [22] In our study, the time-dependent upregulation of CCL2 and CCL3 during SDC1−/− DC maturation may also be account for increased recruitment of leucocytes explaining the observed increased cellular infiltrate in the CHS reaction in SDC1−/− mice (Figure 2A).…”
Section: Discussionsupporting
confidence: 58%
“…[14] CCL2 amplify and maintain inflammation through chemokine-cytokine networks after the recruitment of circulating leucocytes. [22] In our study, the time-dependent upregulation of CCL2 and CCL3 during SDC1−/− DC maturation may also be account for increased recruitment of leucocytes explaining the observed increased cellular infiltrate in the CHS reaction in SDC1−/− mice (Figure 2A).…”
Section: Discussionsupporting
confidence: 58%
“…This pathway has been shown to evoke ICD in melanoma, acute-promyelocytic leukemia, and pancreatic cancer models ( 31 ). Most recently, this concept has been shown to be important in neutrophil-based anticancer activity, where apoptotic cancer cells release epigenetically regulated cytokines such as CXCL1, CXCL10, and CCL2, driving nucleic acid-elicited phagocytosis of dying cancer cells by neutrophils ( 13 , 110 , 111 ).…”
Section: Discussionmentioning
confidence: 99%
“…These molecules recruit circulating leukocytes into the inflamed tissue and activate various cell types via engagement of cell surface receptors [ 69 , 120 ]. Of the four chemokine families, CC-chemokines are the most well-established regulators of neuropathic pain [ 30 , 121 , 122 , 123 ]. In particular, many studies have demonstrated that CCL2 is upregulated in macrophages and damaged Schwann cells following nerve injury [ 26 , 51 , 124 , 125 ], and pharmacological or genetic inhibition of CCL2 and/or its receptor CCR2 markedly alleviates neuropathic pain [ 126 , 127 , 128 ].…”
Section: Roles Of Cytokines and Chemokines In Neuropathic Painmentioning
confidence: 99%
“…Recently, CCL3 (macrophage inflammatory protein-1α, MIP-1α) and CCL4 (MIP-1β) have been shown to be upregulated in macrophages and Schwann cells following nerve injury, and to play critical roles in orchestrating long-lasting neuroinflammation in the peripheral nervous system [ 23 , 30 , 123 , 129 ]. Because their receptors (CCR1 and CCR5) are also expressed on macrophages and Schwann cells, CCL3 and CCL4 can act in an autocrine fashion to drive intracellular signaling for upregulation of inflammatory molecules such as IL-1β.…”
Section: Roles Of Cytokines and Chemokines In Neuropathic Painmentioning
confidence: 99%